Lactoferrin improves cognitive function and attenuates brain senescence in aged mice. (February 2020) - Zheng, Jiaping; Xie, Yunzhen; Li, Fei; Zhou, Yu; Qi, Liqin; Liu, Libin; Chen, Zhou
Graphical abstract: Highlights: Lactoferrin improves memory and learning ability of naturally aged C57/BL6J mice. Lactoferrin alleviates oxidative stress and inflammatory responses in aged mice. Lactoferrin decreases iron deposits in the brains of aged mice. Metabolism alterations in the hippocampi of aged mice were partially reversed by lactoferrin intervention. Abstract: Lactoferrin (LF) has been shown to be effective in attenuating some aging-related changes, although its potential in alleviating aging-related cognitive decline remains to be clarified. In this study, we evaluated the effects of LF (2000 mg/kg/day for 3 months) on the cognitive ability of 16-month-old C57/BL6J mice. Spatial cognition was improved in aged mice after LF administration, with more pyramidal cells detected in the hippocampi, and more regular distribution. LF also reduced iron deposition, malondialdehyde (MDA) and ROS levels in the hippocampus. Similarly, LF decreased the expression of two subunits of NAPDH oxidase: Gp91phox and P22phox, and reduced hippocampal and serum levels of IL-1β, IL-6 and TNF-α in aged mice. Metabolomic analysis revealed alterations in LysoPG, LysoPS, xanthine, adenosine and oxypurinol, which were partially reversed by LF. The potential of LF to protect cognitive function in aged animals offers a unique pharmacological approach for neurodegenerative disorders associated with aging.